(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Various cultures take place in the development of the philosophical thought of mankind. These cultures complemented each other and made a worthy contribution to the development of science. In this respect, the invaluable legacy of Muslim thinkers has served the progress of humanity. In their works, thinkers not only improved the thinking of antiquity, but also connected it with the principles of Islamic teaching. Later European philosophical thought benefited from these views. The works of geniuses such as Ibn Sina, Ibn Rushd, al-Ghazali, who contributed to world civilization, are still in the focus of researchers.